2016
DOI: 10.4238/gmr.15016050
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect and mechanism of hydrogen treatment on lung epithelial barrier dysfunction in rats with sepsis

Abstract: ABSTRACT. This study aimed to explore the protective effect of hydrogen and to investigate the underlying mechanism of its preliminary effect on the alveolar epithelial barrier function in septic rats. Forty-five male SpragueDawley rats were divided randomly into three groups (N = 15): control [saline injection (intraperitoneal, ip), air drawing; SA], acute lung injury group [lipopolysaccharide (LPS) injection (ip, 15 mg/kg), air drawing; LA], and acute lung injury combined with hydrogen drawing group [LPS inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…Considering the high mortality of endotoxemia, in order to determine the best time for hydrogen treatment, we referred to the previous literature (22)(23)(24)(25) and firstly observed the 7day survival rate of animals. Thirty-three mice were randomly selected from the hydrogen treatment group and divided into three groups: hydrogen treatment after 30 min of LPS (n = 11), hydrogen treatment after 6 h of LPS (n = 11) and hydrogen treatment after 12 h of LPS (n = 11).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Considering the high mortality of endotoxemia, in order to determine the best time for hydrogen treatment, we referred to the previous literature (22)(23)(24)(25) and firstly observed the 7day survival rate of animals. Thirty-three mice were randomly selected from the hydrogen treatment group and divided into three groups: hydrogen treatment after 30 min of LPS (n = 11), hydrogen treatment after 6 h of LPS (n = 11) and hydrogen treatment after 12 h of LPS (n = 11).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…In the L15 group, the levels of SDC-1, ICAM-1 and PVPI in group Y were not significantly different compared to group N, indicating that the endothelial polysaccharide coating structure in critically ill patients was severely damaged and could not be restored by ulinastatin alone. Due to the damage of endothelial polysaccharide coating, the increase in capillary permeability, the release of inflammatory factors and the exudation of alveolar capillaries in sepsis patients, the volume of extravascular lung water (EVLW) is increased in sepsis patients [23]. PVPI can adequately reflect the permeability of pulmonary capillaries and the value of PVPI was not increased over an increased blood volume [24].…”
Section: Baseline Characteristics Of the S15 Patients In Treatment (Y) And Control Groups (N)mentioning
confidence: 99%
“…Many studies have investigated how molecular hydrogen alleviates the physiological barrier damage caused by sepsis, including protective effects on vascular endothelial cells30, 35, 36, epithelial cells (e.g., alveoli and gastrointestinal epithelium)9, 11, 29, 37 and intercellular junctions9, 30, 33, 38, which are characterized by decreased permeability, increased transmembrane resistance, and regulation of expression and distribution of intercellular junction- related proteins.…”
Section: Molecular Hydrogen Reduces the Physiological Barrier Dysfuncmentioning
confidence: 99%
“…Similar to vascular endothelial cells, HRS has a protective effect on epithelial cells. Studies by Zhang et al11 and Liu et al37 have demonstrated that HRS attenuates the alveolar epithelial barrier damage caused by LPS, improves alveolar gas exchange, and reduces cell damage caused by alveolar epithelial cell apoptosis and excessive autophagy. Yang et al9 and Ikeda et al29 reported that molecular hydrogen also protects the gastrointestinal epithelial barrier during sepsis.…”
Section: Molecular Hydrogen Reduces the Physiological Barrier Dysfuncmentioning
confidence: 99%